Historical coverage of the socio-economic life of Afghan citizens in Turkistan (The second half of the xix century – the beginning of the XX century) - Mattiev Utkir Begmatdulobovich (Research Parks Publishing LLC, 2020)
The end of the XIX and the beginning of the XX centuries was distinguished from other centuries by its splendor in the civilization of mankind.The rapid development of capitalist relations and the influence of colonial wars, inspired by capitalist relations, did not cease to affect both Central Asia and its adjacent territory Afghanistan.These territories became the robbed territory between the Great Britain and the Russian Empire of the great imperialist countries. Because of the rich raw materials and resources, cheap labor force and economic base, this area remained undeveloped because of the low development of Science in the khanates, both empires could serve as a decisive material basis for the development of their economy.However, in the period under study, the gross development of capitalist relations was the main impetus for the policy of colonialism, which was the main means of replenishing the raw material base of states.As a result, the British and Russian Empire entered with the zeal of power there in order to take the khanates into their sphere of influence.For this purpose, many military and ambassadorial missions were organized by the empires. The relevance of this research work is that the object of the scientific research conducted so far is focused on more and more political activities, and since the participation of Afghan citizens living in the political life of society in Central Asia has been poorly studied, the focus has been on the social and economic life of Afghans as the main subject.Different political processes, due to social economic pressures, the Afghan citizens who came to the region of Turkistan and live permanently or temporarily among other nations also had their rightful place in the socio-economic and political life of the country.Their activity was preserved in various scientific literature, in the Central State Archive of the Republic of Uzbekistan with the corresponding figures.It is beyond doubt that these sources justify the veracity of the information presented.Therefore, the sources related to the period under study are analyzed accordingly, it was studied and used in scientific research work.